Financial feasibility analysis of pickled skipjack tuna products in Micro, Small, and Medium Enterprises (MSMEs) in Gorontalo City (Case study of Mutfood Indonesia) - Imam Prawiranegara Gani; Andi Desiah Pradilia (Universitas Malikussaleh, 2026)
This study aims to analyze the financial feasibility of a pickled skipjack tuna product business at Mutfood Indonesia, a Micro, Small, and Medium Enterprise (MSME) in Gorontalo City. The feasibility analysis was conducted through calculations of investment costs, operational costs, revenue, and financial feasibility indicators consisting of Break Even Point (BEP), Revenue Cost Ratio (R/C Ratio), and Payback Period (PP). The results showed that Mutfood Indonesia requires a total initial investment cost of IDR 500,904,000 to support the production process. With a selling price of IDR 50,000 per package and a production capacity of 2,000 packages per month, this business earns a net profit of IDR 39,204,037.00 per month. The R/C Rasio is 1,62 or the value is above 1, indicating that each cost expenditure is able to generate greater revenue and indicates that the business is financially feasible. The BEP calculation illustrates that the break-even point is reached at 467 units or IDR 23,350,000, which indicates that Mutfood Indonesia's production volume far exceeds the minimum limit to cover operational costs. Meanwhile, the Payback Period analysis results show a return on investment of 13 months, which is relatively fast for an MSME. Compared with previous research, these results are consistent with previous research, where fishery processing businesses with an R/C value > 1 and a relatively short payback period indicate profitable business prospects. Overall, this study concludes that Mutfood Indonesia's pickled skipjack tuna business is feasible and has potential for future development. Keywords: BEP; MSMEs; Payback Period; Pickled Skipjack Tuna; R/C Ratio